Desmoid tumors: to treat or not to treat, that is the question - Kasper, Bernd; Raut, Chandrajit P.; Gronchi, Alessandro (Cancer, 2020)
Desmoid tumors (DTs) are a rare disease of intermediate malignancy characterized histologically by a locally aggressive, monoclonal, fibroblastic proliferation and clinically by a variable and often unpredictable course. For decades, surgical resection has been the standard initial treatment approach; however, more recently, a paradigm shift toward a more conservative treatment strategy has been introduced. More than 5 years ago, The Desmoid Tumor Working Group started a consensus initiative in Europe with the aim of harmonizing the strategy among clinicians and setting up treatment recommendations for patients with DTs. This review summarizes the latest joint, global, evidence-based guideline approach to DT management. Moreover, a number of gray areas in the treatment recommendations are discussed, and possible future perspectives on the treatment armamentarium for patients with DTs are presented.
Gesehen am 11.08.2021